2020
DOI: 10.17582/journal.aavs/2020/8.8.873.881
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Fermentation and the In Vitro Digestibility Characteristics of Agricultural Waste-Based Complete Feed Silage with Cellulase Enzyme Treatment

Abstract: The use of crop residues and agricultural wastes in animal feed is a very common practice to ensure a feed supply in livestock production. However, the agricultural wastes generally have high crude fiber content. The study aimed at establishing the effects of increasing cellulase levels on fermentation quality, chemical composition, and in vitro nutrient digestibility of complete feed silage containing oil palm frond and rice crop residue. The mixture of ingredients (king grass, rice crop residue, oil palm fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 0 publications
3
13
0
Order By: Relevance
“…It was observed that cellobiohydrolase enzyme produced from Pichia pastoris yeast originating from Lentinula edodes fungus increased the cellulose digestibility of rice, wheat, and corn straws (Li et al, 2019). Santoso et al (2020) revealed that increasing cellulase doses increased the in vitro dry matter, in vitro organic matter, and NDF digestibility of silage made from agricultural waste (Table 1).…”
Section: Enzymesmentioning
confidence: 98%
See 1 more Smart Citation
“…It was observed that cellobiohydrolase enzyme produced from Pichia pastoris yeast originating from Lentinula edodes fungus increased the cellulose digestibility of rice, wheat, and corn straws (Li et al, 2019). Santoso et al (2020) revealed that increasing cellulase doses increased the in vitro dry matter, in vitro organic matter, and NDF digestibility of silage made from agricultural waste (Table 1).…”
Section: Enzymesmentioning
confidence: 98%
“…Recently, it has been reported that exogenous fibrinolytic enzymes increase the digestibility of feeds in in vitro rumen digestion studies (Kondratovich et al, 2019;Li et al, 2019;Santoso et al, 2020). Factors such as the mode of action of exogenous enzymes, the type of animal used, compatibility between exogenous enzymes, and rumen microflora affect the enzyme activity.…”
Section: Enzymesmentioning
confidence: 99%
“…For normal fiber degradation, rumen pH is around 6,0-7,0. At pH 6.2, the rate of microbes' degrading fiber activity will decrease [4]. The fermentation process on complete feed can reduce lignin content so that microbes can easily degrade feed.…”
Section: Rumen Phmentioning
confidence: 99%
“…A previous study showed that complete feed with rice straw levels of 25%, 30%, 35%, and 40% without fermentation produced 60.93-64.53% IVDMD, 62.92-65.56% IVOMD and 110.00-122.50 mM total VFA concentration. Complete feed with a 40% rice straw level resulted in the lowest IVDMD, IVOMD, and VFA total concentration [4]. Furthermore, there have not been many studies related to the effect of Moringa leaves on methane gas production.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation